Educating the Concepts of Retention Factor of a Company with the Case of Employee Engagement Level Increase - Tsareva, Natalia A. (2020)
The current socio-economic situation creates similar conditions and rules for companies in various industries around the world.in this vein, the study and educate the retention factors of the company are of a great importance.  The task of staff productivity increase and the overall effectiveness of its activities is relevant. The most important role in addressing the issue of employee productivity and performance increasing, as well as his retention is played by employee engagement. The researchers studying engagement at work recognize that this phenomenon is multifaceted and define it as an employee's physical, cognitive and emotional state, causing excessive performance of his functional duties. Involvement is interconnected with the motivational potential of work, therefore, the conditions for the engagement development are the following ones: work significance and diversity, the comparison of work with its result. The authors of the article conducted the study of engagement at work in the enterprises of fishing and fish processing industries. We determined the problems that impede the growth of staff engagement. The authors of the article implemented the program of corrective actions aimed to improve the factors affecting the engagement at work and retention of staff. We determined the interdependence of involvement level and the coefficient of staff turnover, as well as the return of employees to some holding.